Co-researching and designing innovative learning approaches in sexuality and relationships education. (2nd July 2020) - Johnson, Bruce; Flentje, Jane; Bartholomaeus, Clare
ABSTRACT: Young people are rarely consulted about what and how they are taught in sexuality and relationships education (SRE) at school. The reasons for this are complex and relate to adults' reluctance to acknowledge the need to take account of students' perspectives on personally sensitive matters. In this article, we provide a brief rationale and justification for enabling students to have a greater say in the design and development of teaching approaches in SRE. We outline, in practical ways, how we used participatory research methods to engage young people in researching and developing innovative teaching and learning resources that utilised their musical, design, artistic, technological and literacy talents. In reflecting on some of the benefits associated with using participative research approaches, we discuss higher levels of student engagement and 'playfulness', an enhanced acceptance of, and respect for, difference and diversity, and the greater use of critical thinking during the research process. The challenges we faced were due to difficulties gaining ethics approval for an emergent research design from a human research ethics committee which insisted on pre-specified research protocols, and due to the pervasive effect of the taken-for-granted practices and ways of doing things in secondary schools that preserve existing power relationships and limit innovation and change. Despite these challenges, we remain positive about the potential of participatory research to provide students with a greater say in their sexuality and relationships education.